RECYCLING NANOARCHITECTONICS OF GRAPHENE OXIDE FROM CARBON FIBER REINFORCED POLYMER BY THE ELECTROCHEMICAL METHOD - Ling, Li; Wu, Chao; Xing, Feng; Memon, Shazim Ali; Sun, Hongfang (Nanomaterials, 2022)
In this paper, an electrochemical method was proposed to recycle nanoarchitectonics of graphene oxide (GO) from carbon fiber reinforced polymer (CFRP). In the recycling process, NaCl solution with varied concentrations (3% and 10%) and tap water were used as electrolyte, while the impressed current density varied from 2.67 A/m2 to 20.63 A/m2. The results indicated that in NaCl electrolyte, the obtained nanoarchitectonics of GO contained a large amount of nano-carbon onions (NCO) produced by etching CFRP, while high purity GO was produced when tap water was used as electrolyte. The higher current density improved the production efficiency and resulted in a finer GO particle size. The proposed recycling method of GO is economical and simple to operate. It also provides an alternate approach to handle discarded CFRP.
Keywords: Type of access: Open Access; GO; CFRP; recycling; electrochemical method; nano carbon onion